Current Status and Reflections on Ocean CO2 Sequestration: A Review - Shanling Zhang; Sheng Jiang; Hongda Li; Peiran Li; Xiuping Zhong; Chen Chen; Guigang Tu; Xiang Liu; Zhenhua Xu (Energies)
Climate change has become one of the most pressing global challenges, with greenhouse gas emissions, particularly carbon dioxide (CO2), being the primary drivers of global warming. To effectively address climate change, reducing carbon emissions has become an urgent task for countries worldwide. Carbon capture, utilization, and storage (CCUS) technologies are regarded as crucial measures to combat climate change, among which ocean CO2 sequestration has emerged as a promising approach. Recent reports from the International Energy Agency (IEA) indicate that by 2060, CCUS technologies could contribute up to 14% of global cumulative carbon reductions, highlighting their significant potential in mitigating climate change. This review discusses the main technological pathways for ocean CO2 sequestration, including oceanic water column sequestration, CO2 oil and gas/coal seam geological sequestration, saline aquifer sequestration, and seabed methane hydrate sequestration. The current research status and challenges of these technologies are reviewed, with a particular focus on the potential of seabed methane hydrate sequestration, which offers a storage density of approximately 0.5 to 1.0 Gt per cubic kilometer of hydrate. This article delves into the formation mechanisms, stability conditions, and storage advantages of CO2 hydrates. CO2 sequestration via hydrates not only offers high storage density but also ensures long-term stability in the low-temperature, high-pressure conditions of the seabed, minimizing leakage risks. This makes it one of the most promising ocean CO2 sequestration technologies. This paper also analyzes the difficulties faced by ocean CO2 sequestration technologies, such as the kinetic limitations of hydrate formation and leakage monitoring during the sequestration process. Finally, this paper looks ahead to the future development of ocean CO2 sequestration technologies, providing theoretical support and practical guidance for optimizing their application and promoting a low-carbon economy.